1996
DOI: 10.1002/pro.5560050820
|View full text |Cite
|
Sign up to set email alerts
|

Conformation and molecular topography of the N‐terminal segment of surfactant protein B in structure‐promoting environments

Abstract: Although the effects of surfactant protein B (SP-B) on lipid surface activity in vitro and in vivo are well known, the relationship between molecular structure and function is still not fully understood. To further characterize protein structure-activity correlations, we have used physical techniques to study conformation, orientation, and molecular topography of N-terminal SP-B peptides in lipids and structure-promoting environments. Fourier transform infrared (FTIR) and CD measurements of SP-B1_25 (residues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 76 publications
(97 citation statements)
references
References 49 publications
(67 reference statements)
8
88
1
Order By: Relevance
“…The structure and surface activity of these peptides have been investigated thoroughly both in vitro and in vivo. The conformation of mSP-B-(1-25) was found to be ␣-helical (21,22). In vitro comparison of the surface activity of mSP-B- with that of dSP-B-(1-25) in a captive bubble surfactometer revealed that both peptides reduced the surface tension, with the dimeric peptide expressing better ability to lower surface tension than the monomeric peptide (23).…”
mentioning
confidence: 99%
“…The structure and surface activity of these peptides have been investigated thoroughly both in vitro and in vivo. The conformation of mSP-B-(1-25) was found to be ␣-helical (21,22). In vitro comparison of the surface activity of mSP-B- with that of dSP-B-(1-25) in a captive bubble surfactometer revealed that both peptides reduced the surface tension, with the dimeric peptide expressing better ability to lower surface tension than the monomeric peptide (23).…”
mentioning
confidence: 99%
“…The SP-C 1±35 peptide was based on the human SP-C sequence and palmitoylated as reported previously [20,22]. The present study group has described conformation of the structure of these peptides [21,22].…”
Section: Synthesis Purification and Formulation Of Surfactant Peptidesmentioning
confidence: 76%
“…Peptides covering different parts of the native molecule have been synthesized and evaluated in vitro and in vivo. Peptides covering the C-terminal part and containing at least 17 amino acids accelerate surfactant spreading and improve static lung compliance in fetal rabbits [16,17] and synthetic replicas of the N-terminal part of the polypeptide chain, in particular positions 1-25, mimic most of the activities performed by native, full length SP-B [18][19][20]. Extrapolation to physiological conditions from the latter studies is difficult since Synthetic Surfactant Protein Analogues Biol Neonate 1998;74(suppl 1):9-14 13 in many experiments PA was the only lipid present, while the amount of PA in surfactant is low.…”
Section: Sp-b Analoguesmentioning
confidence: 99%